Down with the roots. Phytoliths as biocultural traces in historical olive agroecosystems of Sicily - Ferrara, Vincenza; Sala, Giovanna; Garfì, Giuseppe; La Mantia, Tommaso; Ekblom, Anneli (Frontiers in Ecology and Evolution, 2025)
Within the multidisciplinary framework of historical ecology, in this study plant morphology, oral history, and soil analyses are combined with phytoliths to reconstruct shifts in management and environment of historical and living olive agroecosystems on the island of Sicily (Italy). The use of phytoliths in the study of historical agroecosystems is still a developing field. We present the collaborative work done on three historical olive agroecosystems (Bosco Pisano, a wild olive wood; Cozzo del Lampo, a Mediterranean olive orchard; Malìa, remnant of past agroforestry), where we have collected and analyzed phytolith assemblages to trace correlations between environmental dynamics and (agri)culture, as unfolding over the latest six millennia. We demonstrate that the cumulative ecological legacies in historical agroecosystems are traceable through phytolith analyses. Bosco Pisano allows for a calibration of the tree cover density, based on phytolith evidence. Meanwhile, Cozzo del Lampo and Malìa have evolved from a shrubland-type of environment to fruit gardens and open grasslands, with establishment of olive trees in between as key vegetation elements. Both these examples show the longevity of combined land uses, especially the grazing adapted olive cultivation in Malìa. In gaining clues on clear variations in land use, as abandonment and intensification, our results demonstrate that phytoliths can shed light also in local past intercultural exchange of knowledge. The integrated methodology presented here allows to appreciate how the biological and cultural diversity in historical agroecosystems has shaped their current state and inspires present-future management.